Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderating : Studi: Perusahaan Manufaktur Sektor Industrials and Consumer Cyclicals - Greacyana Ressa Naisau; Petrus Emanuel De Rozari; Filipus Argentano Guntur Suryaputra (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the effect of financial performance on firm value with dividend policy serving as a moderating variable in manufacturing companies within the industrials and consumer cyclicals sectors listed on the Indonesia Stock Exchange during the 2019–2023 period. A quantitative approach was employed using secondary data obtained from the companies' annual financial statements. The sample was selected through a purposive sampling technique, resulting in 21 companies with a total of 105 observations. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) to examine both the direct effects of financial performance and the moderating role of dividend policy. The findings indicate that profitability has a positive but insignificant effect on firm value. In contrast, liquidity and leverage have positive and significant effects on firm value. Simultaneously, profitability, liquidity, and leverage significantly influence firm value. Dividend policy is able to moderate the effects of profitability and leverage on firm value but fails to moderate the relationship between liquidity and firm value. Furthermore, dividend policy has a negative but insignificant direct effect on firm value. These findings suggest that dividend policy can strengthen the influence of certain financial performance indicators on firm value and should therefore be considered by both corporate management and investors in making strategic financial and investment decisions.